2020
DOI: 10.1007/s11768-020-9195-1
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative control and communication of intelligent swarms: a survey

Abstract: Individuals exchange information, experience and strategy based on communication. Communication is the basis for individuals to form swarms and the bridge of swarms to realize cooperative control. In this paper, the multi-robot swarm and its cooperative control and communication methods are reviewed, and we summarize these methods from the task, control, and perception levels. Based on the research, the cooperative control and communication methods of intelligent swarms are divided into the following four cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…After many experiments, for the data set, the traditional clustering algorithm will appear multiple times in the data results, we might as well use it to express the performance of traditional k -means [ 20 ]. However, the performance of the k -means plus algorithm is not only stable, but sometimes better than k -means; the advantage will be basically the same as k -means, and there is only a small probability that it will be inferior to the traditional k -means algorithm [ 21 ]. Here is a preliminary experimental probability value, which is defined as follows: …”
Section: Good Life and Coordinated Development Research Methods Based On Intelligent Communication And K -Means Algorimentioning
confidence: 99%
“…After many experiments, for the data set, the traditional clustering algorithm will appear multiple times in the data results, we might as well use it to express the performance of traditional k -means [ 20 ]. However, the performance of the k -means plus algorithm is not only stable, but sometimes better than k -means; the advantage will be basically the same as k -means, and there is only a small probability that it will be inferior to the traditional k -means algorithm [ 21 ]. Here is a preliminary experimental probability value, which is defined as follows: …”
Section: Good Life and Coordinated Development Research Methods Based On Intelligent Communication And K -Means Algorimentioning
confidence: 99%
“…The resource allocation with minimized redundancy upholds the systematic efficiency and sustainability. 147 AI-enhanced swarm intelligence promotes continuous improvement in coordinating and collaborating MNRs. By leveraging AI, adaptive decision-making ability based on environment dynamics requirements can be obtained.…”
Section: Collective Behaviormentioning
confidence: 99%
“…The resource allocation with minimized redundancy upholds the systematic efficiency and sustainability. 147…”
Section: Intelligent Robotics In Microfluidicsmentioning
confidence: 99%
“…According to Equation (11), after obtaining the maximum Q-function, we need to derive the optimal policy. Using the recursive mechanism, the Q-function can be updated as [36]…”
Section: Dqn-based Control Algorithmmentioning
confidence: 99%
“…In this literature, it showed that different approach combinations would provide the researcher with suitable knowledge regarding both the benefits and deficiencies. Kun et al [11] divided the collaborative control and communication methods of intelligent swarms into the following four categories: task assignment-based methods, bioinspired methods, distributed sensor fusion, and reinforcement learning-based methods. Based on the basic ideas and introduction of different methods, the future development stages of intelligent group cooperative control and communication are forecasted, and the problems and challenges are put forward.…”
Section: Introductionmentioning
confidence: 99%